Liver transplantation in the out of home treatment program in the state of Sergipe in 2008. Clinical analysis and costs - Leal, Bianca Souza; Nascimento, Tereza Virgínia Silva Bezerra; Figueiredo, João Augusto Guimarães; França, Alex Vianey Callado (Brazilian Journal of Transplantation, 2010)
Introduction: In Brazil, liver transplantation is performed mainly in the Southeast region. In states where there is no liver transplantation service, such as Sergipe, patients of the National Health System are driven to other states, and such expenses are funded by the Out of Home Treatment Program (TOH). Purpose: The aim of this study was to set main aspects of patients referred to liver transplantation and the costs of services funded by TOH in Sergipe along 2008. Methods: Analysis of 55 records of patients who were registered in TOH in Sergipe during 2008. Age, gender, origination, place of birth of the patients, presence of cirrhosis and death in 2008 were assessed. Carers, donors and patients’ features and their costs were compared, as well as transplanted versus non-transplanted patients. Some additional costs of those patients were also analyzed. Results: Most patients were men (63.6%), with ages between 12 and 59 (61.8%) from Aracaju/ SE (50.9%), and 49.1% came from the country area of Sergipe. About 80% of patients presented cirrhosis, and 12.7% died along 2008. The main causes of cirrhosis were hepatitis C and alcoholism, both in 15.9% of cases. Liver transplantation was performed in 30.9% of patients, and 76.5% of those transplantations were performed in São Paulo. Carers caused higher TOH expenditures. R$ 217,575.72 from a total amount of R$ 442,088.43 included patients and donors. The average cost of each patient funded by TOH was R$ 8,037.97 or R$ 10,590.49, with additional costs included. Patients traveled an average of 4.76 times in 2008, and the transplanted patients spent 1.8 times more than non-transplanted patients. Conclusion: Hepatic cirrhosis was the major cause for the TOH indication. It was concluded that the cost of the program was around R$ 8,000.00 per patient in 2008. Based on this figure, a pre- and post-liver transplantation service could be created at the state level.